#TITLE_ALTERNATIVE# - RACHMAN (NIM 10103008), ADITYA
Value determination of European barrier option can be done analytically and numerically. First of all, a model which is used to determine value of European barrier option will be derived in partial differential equation form. By using solving method for Cauchy problem, partial differential equation for European barrier option can be solved analytically. In determining value of American barrier option, it can be built a non-homogen partial differential equation which represent an American barrier option. By solving that equation, value of American barrier option can be determined. Furthermore, by using Crank-Nicolson method, partial differential equation model for European barrier option can be solved numerically, so an approach value of European barrier option can be determined.